If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + 73 = -22 Reorder the terms: 73 + r = -22 Solving 73 + r = -22 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-73' to each side of the equation. 73 + -73 + r = -22 + -73 Combine like terms: 73 + -73 = 0 0 + r = -22 + -73 r = -22 + -73 Combine like terms: -22 + -73 = -95 r = -95 Simplifying r = -95
| 0.06(6y-3)+0.02y=0.10y-0.5 | | 3x-2y-3x= | | 5-7x=23 | | 13b=117 | | 6(u+6)-2u=8 | | 10/c=150/200 | | 2(x+1)+5=4x-2(-3+x) | | -5v=-85 | | -8x+4(x-4)=-28 | | x-5/2x/5-x/6x | | 4(2y+1.5)+1=2(2y+1.5)+3y+4 | | 0.02x+0.45(50)=36.5 | | 4f=8 | | 4-5(-4n+3)=16 | | 0.04x+0.09y= | | 3/8/-1/6 | | 3/8/1/6 | | 2(3n+5)=8(3n+1)+8 | | 3/8(-1/6) | | 2x+10=87 | | 1/2.5•2.5/1 | | 0.05n+0.1d=1.30 | | (3/16)=(1/(2x)^2) | | 0.05n+0.1d= | | 2/15x-7/5=1 | | 1/6÷3/8 | | -3y-10=8y+12 | | 3/8÷1/6 | | (3/8)=(1/x) | | -2(7-n)+4=12 | | 16x=20x-13 | | -16x^2+48x+0=20 |